Review paperThe lanolin paradox phenomenon - Żmudzińska, Maria; Czarnecka-Operacz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2008)
The problem of lanolin contact allergy is still widely discussed in the literature. Wolf described four lanolin paradoxes. They characterize lanolin in respect of its potential to evoke allergy and indicate the necessity for further investigations concerning the development of delayed type of hypersensitivity both in the general population and in patients with chronic inflammatory dermatoses.